Community-Based Integrated Water Resources Conservation on Mount Penanggungan in Pasuruan, Jawa Timur - Muhammad Chrisna Satriagasa; Ambar Kusumandari; Hatma Suryatmojo; Faizal Nur Fahmi; Uswatun Chasanah (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2022)
Mount Penanggungan’s watershed ecosystems, which play a crucial role in managing the water cycle, are in an alarming state right now. Community-based integrated water resources conservation efforts aim to restore the function of watersheds, particularly in terms of controlling the water cycle. The purpose of this article is to describe a variety of community-based water conservation efforts in Mount Penanggungan, Gempol District, Pasuruan, East Java. We encourage the local community to engage in integrated water resource conservation activities, such as engineering efforts, plastic waste processing, tree planting, education, and public awareness-raising. Community service students from UGM participate in these programs as live-in facilitators. Local communities now have the infrastructure necessary to engage in community-based water conservation, including both physical and non-physical infrastructure (biopore and rainwater harvester) but also non-physical infrastructure (awareness and knowledge). This activity must be continued in order to observe the growth and outcomes of the empowerment initiatives that have already been carried out.